A Learning Management Model. Profe Influencer - Rivera-Rogel, Diana; Andrade, Lucy; Iriarte, Margoth; Beltrán, Ana María; Piedra, Nelson (Journal of Ecohumanism, 2025)
A learning management model highlights the relationship between education, technology and the democratization of knowledge. Technology is presented as an essential tool to enhance the educational experience and expand the possibilities of access to information and knowledge. This article focuses on the importance of education as a relevant social variant in the configuration of individual and collective values, as well as in the democratization of access to knowledge. It addresses media literacy as an essential competence for active participation in society and highlights how formal, non-formal and informal education play key roles in educational development. A model of learning management through digital platforms is established, with a focus on criteria such as the delimitation of the learning object, the search and organization of data through YouTube, and the creation of a platform that hosts a selection of more than 1,000 YouTube videos. The website https://profeinfluencer.utpl.edu.ec/, is consolidated as an initiative of the Universidad Técnica Particular de Loja to strengthen virtual education through resources and teaching and learning strategies.